2017
DOI: 10.1111/ddi.12520
|View full text |Cite
|
Sign up to set email alerts
|

Joint species models reveal the effects of environment on community assemblage of freshwater mussels and fishes in European rivers

Abstract: Aim Given that riverine systems exhibit longitudinal environmental gradients from headwater to the mouth of a river, habitat heterogeneity appears to be a major driver of spatial variation in community composition among riverine localities. As freshwater ecosystems are amongst the most endangered ecosystems in the world, community‐based conservation and multiple‐species management are necessary to maintain ecosystem integrity. We used joint species distribution models (JSDMs) to investigate the relative import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 64 publications
4
31
0
3
Order By: Relevance
“…Tikhonov et al, 2017). Studies applying joint models to freshwater communities suggest that shared responses to environmental conditions may be more important in determining community composition than residual correlations between taxa (Inoue, Stoeckl, & Geist, 2017;Pollock et al, 2014;Royan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tikhonov et al, 2017). Studies applying joint models to freshwater communities suggest that shared responses to environmental conditions may be more important in determining community composition than residual correlations between taxa (Inoue, Stoeckl, & Geist, 2017;Pollock et al, 2014;Royan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As most populations of M. margaritifera are already associated with some kind of protected area, albeit with typically weak levels of protection, the most useful strategy is to increase protection by upgrading the respective protection categories to provide stricter protection for the landscape. This is likely to mitigate further habitat degradation and population loss because M. margaritifera populations are adversely affected by even slight changes in the substrate conditions of streams (Geist & Auerswald, 2007) and in stream nutrient levels (this study ;Bauer, 1988;British Standards Institution, 2017;Inoue et al, 2017). In contrast, the greater tolerance of U. crassus to substrate conditions and nutrient input, as well as the greater spectrum of host fish species, will in most cases not require an extremely strict legal protection category.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study found associations between the occurrence of mussel species and their fish hosts, as well as a relationship between environmental factors and mussel occurrences (Inoue, Stoeckl, & Geist, ). The same study hypothesized that mussel distributions are nested within the host fish distributions and that the presence of mussels at a given site is primarily driven by local abiotic conditions.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations